Reliability of wearable inertial measurement units to measure physical activity in team handball - Luteberget, L. S.; Holme, B. R.; Spencer, M. (International Journal of Sports Physiology and Performance, 2018)
To assess the reliability and sensitivity of commercially available inertial measurement units to measure physical activity in team handball. Method: Twenty-two handball players were instrumented with 2 inertial measurement units (OptimEye S5; Catapult Sports, Melbourne, Australia) taped together. They participated in either a laboratory assessment (n=10) consisting of 7 team handball-specific tasks or field assessment (n=12) conducted in 12 training sessions. Variables, including PlayerLoad™ and inertial movement analysis (IMA) magnitude and counts, were extracted from the manufacturers` software. IMA counts were divided into intensity bands of low (1.5-2.5 m/s), medium (2.5-3.5 m/s), high (>3.5 m/s), medium/high (>2.5 m/s), and total (>1.5 m/s). Reliability between devices and sensitivity was established using coefficient of variation (CV) and smallest worthwhile difference (SWD). Results: Laboratory assessment: IMA magnitude showed a good reliability (CV=3.1%) in well-controlled tasks. CV increased (4.4-6.7%) in more-complex tasks. Field assessment: Total IMA counts (CV=1.8% and SWD=2.5%), PlayerLoad (CV=0.9% and SWD=2.1%), and their associated variables (CV=0.4-1.7%) showed a good reliability, well below the SWD. However, the CV of IMA increased when categorized into intensity bands (2.9-5.6%). Conclusion: The reliability of IMA counts was good when data were displayed as total, high, or medium/high counts. A good reliability for PlayerLoad and associated variables was evident. The CV of the previously mentioned variables was well below the SWD, suggesting that OptimEye`s inertial measurement unit and its software are sensitive for use in team handball.